Indwelling pleural catheters in hepatic hydrothorax - Diab, Khalil (2019)
Background Treatment of hepatic hydrothorax (HH) generally involves sodium restriction, diuretics, and serial thoracentesis. In more advanced cases, transjugular intrahepatic portosystemic shunt and liver transplantation may be required. Previously, indwelling tube drainage has been avoided due to concerns regarding high complication rates and overall poor outcomes. Recently, indwelling pleural catheters (IPCs) have been proposed as a novel treatment option for HH. Methods This study was a retrospective review of patients who had undergone IPC placement for HH over a 10-year period at a large liver transplant referral center. We tracked outcomes, including complication rates and liver transplantation, as well as biomarkers of nutritional status. Results Sixty-two patients underwent IPC placement between 2007 and 2017, with 33 IPCs (53%) placed as a bridge to liver transplantation. Complications were recorded in 22 patients (36%); empyema was the most common, diagnosed in 10 patients (16.1%). Ten patients evaluated for liver transplantation underwent successful transplantation following IPC placement. There were statistically significant decreases in both BMI and serum albumin levels following IPC placement. Conclusions IPCs represent a potential treatment for refractory HH and should be used with caution in patients eligible for liver transplantation. Ideally, IPC use for these patients would be evaluated by a multidisciplinary team. IPC use may lead to small decreases in BMI and serum albumin levels in patients over time.